Forming and strengthening factors of personal growth initiatives in life - Saraswati, Putri; Amalia, Sofa; Puspita Arwan, Artiarini (Jurnal Ilmiah Psikologi Terapan, 2023)
Personal Growth Initiative (PGI) helps individuals become mentally healthy because PGI is an active and conscious process by which individuals develop into better people. This study aims to determine the factors that form PGI in individuals at each stage of human development. The research subjects were 141 men and 256 women, taken by stratified random sampling. The research method used was a mixed method. Research data were collected using the PGI scale and analyzed using descriptive and correlational statistics; qualitative questions were analyzed using thematic analysis. Based on the results of the quantitative analysis, it is known that the more an individual matures, the better his PGI. In adolescence and middle adulthood, PGI is related to gender, while in early adulthood, it is related to education. The results of the qualitative analysis show that the personal growth initiatives forming factors in the participants’ lives are religiosity, achievement goals, pro-sociality, social support, self-esteem, and personal responsibility. Furthermore, the reinforcing factors of PGI are self-reflection and self-efficacy, modeling, religiosity, and self-control.